Faktor-Faktor yang Mempengaruhi Penggunaan Obat Herbal dan Obat Tradisional pada Pasien Hipertensi - Sahanaz Zaqiyah Darozah; Dwi Aulia Ramdini; Afriyani; Oktafany (Medula, 2024)
The use of traditional medicine derived from various types of plants has become a culture and tradition in Indonesia. It is primarily used for treating metabolic and degenerative diseases, with hypertension being one of the notable examples. Hypertension stands as a leading cause of premature death worldwide. The global incidence of hypertension in 2015 reached 1.13 billion, with a prevalence ranging between 30-45%. Currently, approximately 75-80% of the world's population with hypertension decide to use herbal medicines because they can be tolerated by the body and have fewer associated side effects. The utilization of herbal and traditional medicines is widespread across various countries, including 29.4% in Iran, 21% in South Africa, 75.6% in Tanzania, 30.6% in Malaysia, and 54%-78% in Indonesia. Therefore, this article discusses factors influencing the use of herbal and traditional medicines among hypertensive patients. Factors known to influence the utilization of these medicines include gender, age, education, occupation, and medication adherence. Health professionals have to be concerned about herbal and traditional medicines use in hypertensive patients to ensure that the treatment is safe, effective, and minimizes the risk of side effects and drug interactions.